2020
DOI: 10.1021/acssuschemeng.0c00442
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Bifunctional NiCo2O4@FeNi LDH Core–Shell Nanoarray Air Electrodes for Rechargeable Zinc–Air Batteries

Abstract: To boost the practical applications of rechargeable Zn−air batteries (ZABs), there is a need to design and synthesize bifunctional air electrodes with high catalytic activity and low cost used in self-supported electrodes. Herein, NiCo 2 O 4 nanocones@ FeNi layered double-hydroxide (LDH) nanosheets with a core− shell hierarchical architecture are prepared by a facile hydrothermal approach and fast electrochemical deposition. The NiCo 2 O 4 nanocones act as scaffolds that provide more reaction sites and acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Summing up, the Cu@NiFe-LDHs/CuF catalyst displayed a high OER activity with an overpotential of 199 mV at 10 mA cm −2 , and good stability of more than 48 h at fixed current densities of 10 and 100 mA cm −2 in 1 M KOH solution. A similar phenomenon was also observed for NiCo2O4@FeNi-LDHs electrode [182]. It was found that, the core NiCo2O4 nanocones acted as scaffolds to offer more reactive sites and accelerate charge transfer to the shell FeNi-LDHs.…”
Section: Hybridizationsupporting
confidence: 75%
“…Summing up, the Cu@NiFe-LDHs/CuF catalyst displayed a high OER activity with an overpotential of 199 mV at 10 mA cm −2 , and good stability of more than 48 h at fixed current densities of 10 and 100 mA cm −2 in 1 M KOH solution. A similar phenomenon was also observed for NiCo2O4@FeNi-LDHs electrode [182]. It was found that, the core NiCo2O4 nanocones acted as scaffolds to offer more reactive sites and accelerate charge transfer to the shell FeNi-LDHs.…”
Section: Hybridizationsupporting
confidence: 75%
“…Synthesis of ZnCo 2 O 4 : A hydrothermal method was used to prepare its hydroxide nanoflowers precursor. [32] 0.297 g Zn(NO 3 ) 2 • 6H 2 O, 0.583 g Co(NO 3 ) 2 • 6H 2 O, and 0.3 g urea were dissolved 40 mL ultrapure water and ethanolene glycol mixture (v/v = 1 : 1) and stirred for 0.5 h. Next, the above solution was transferred to a hydrothermal reactor and kept at 120 °C for 3 h. Then ZnCo 2 O 4 precursor was ultrasonically cleaned in deionized water, dried, and thoroughly ground. Finally, the ZnCo 2 O 4 precursor was put into a muffle furnace for annealing and maintained at 400 °C for 2 h. ZnCo 2 O 4 powder was obtained after natural cooling.…”
Section: Synthesismentioning
confidence: 99%
“…Even though cobalt oxides and cobalt-nickel oxides (NiCo 2 O 4 ) with various nanostructures (1D nanowires, 2D nanosheets, and 3D nanocages) have been developed for broad electrochemical and electrocatalytic applications due to their high inherent electroactivities, good corrosion resistance and ready resources, the insufficient OER activity and relatively large OER overpotential still limit the electrochemical performance of ZABs. [47,72,73] In special, transition metal (Ni, Co, Fe, Mn)-based layered double hydroxides (LDHs) with prominent OER catalytic activity have recently attracted attention. [74] Guo et al developed binder-free air electrodes based on a coreshell structure with NiMn LDH nanosheets as the shells and NiCo 2 O 4 nanowire arrays as the cores that in situ grown on NF via hydrothermal process followed by annealing and co-deposition method (Figure 3d).…”
Section: Metallic Foam/mesh-based Fzabsmentioning
confidence: 99%